Relation Between Different Grade of Pterygium and Amount of Induced Corneal Astigmatism - Mohammad Aamir Khan, Fawad Ahmad, Mohammad Khalid Bin Saleem, Shahid Nazeer, Zubair Ullah Khan, Muhammad Sajid Munir, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: In the present study an attempt was made to assess the effect of pterygium excision on the induced astigmatism, and the relationship between the size of pterygium and the amount of astigmatism. Study Design: Cross-sectional study Place and Duration: Conducted at Jinnah International Hospital during from March 2021 - September 2021. Methods: There were fifty five patients of both genders were presented in this study. Patients were aged between 20-65 years. After obtaining informed written permission, we collected demographic data on all of the participants, including their age, gender, place of residence, and job title.All the included patients in this study had pterygium. The paired t-test was used to compare data from before and after surgery. One-way analysis of variance was used to compare preoperative astigmatism to the grade of pterygium. SPSS 24.0 was used to analyze all data. Results: Among 55 patients, 30 (54.5%) were males and 25 (45.5%) were females. Mean age of the patients was 35.9±15.45 years. There were 32 (58.2%) patients had urban residency and 23 (41.8%) cases had rural residency. Majority of the patients were outdoor workers 38 (69.1%). Majority of the eyes had grade II pterygia 24 (43.6%), 17 (30.9%) patients had grade III and 12 (21.8%) had grade IV pterygia and 2 (3.6%) had double headed pterygia. Pre-operative mean astigmatism in eyes with grade II was 3.43± 1.34D, in eyes of grade IIImean astigmatism was 4.83 ±1.62D and in eyes of grade IV 8.78±2.39D decreases to 1.5±2.18D, 1.56±3.61D and 5.11±4.32D. We found visual acuity same in 26 (47.3%) and improvement in 29 (52.7%) eyes from 0.50± 1.41 D to 1.1±0.56 D. Refractive cylinder was improved to 2.91±2.61D with p vale <0.003. Conclusion: In this study, we found that as the pterygium grows in size, so does the degree of induced astigmatism. A successful pterygium surgery lowers the astigmatism caused by the pterygium and enhances visual acuity.